Holistic Life Concept as the Main Psychological Neoplasm of the Late Maturity Period - N. Chueva, Elena; S. Shuchkovskaya, Elena; A. Tyagunova, Elena; A. Kulik, Anastasia; S. Shiryaeva, Anelia (International Journal of Psychosocial Rehabilitation, 2020)
The problem of the psychological conditions for the constructive development of the personality in the period of late maturity remains one of the most important problems of modern psychology in connection with the actualization of the idea of self-realization and the demand for each individual in society.